ChemInform Abstract: A Gold(I)‐Catalyzed Substituent‐Controlled Cycloisomerization of Propargyl Vinylethers to Multi‐Substituted Furofuran and Furopyran Derivatives. Issue 37 (August 2016) - Liu, Yongxiang; Jin, Shengfei; Wang, Yanshi; Cui, Shanshan; Peng, Xiaoshi; Niu, Yuanyuan; Du, Chuan; Cheng, Maosheng
Abstract: Compounds (IIIa), (IIIc), (IIIe), (Va), (Vc), (VIa), (VII), (VIIIa), and (IX) show antifungal activity.